TurkishLex:Development of a Context-Aware Spell Checker for Detecting and Correcting Spelling Errors in Turkish Texts - Savcı, Pınar; Daş, Bihter (Sakarya University, 2024)
In Turkish, correct spelling correction is crucial for effective communication and preserving the integrity of written text. The challenge lies in the complexity of Turkish morphology and spelling, which can lead to frequent and diverse spelling errors. This study presents a spelling checker adapted for Turkish by creating a new Turkish dataset. The proposed spelling checker model effectively captures both minor and major textual changes and can detect the error. Our findings show that the proposed spelling checker system provides high accuracy and reliability with 98.21% accuracy performance with the Symspell module in correcting Turkish texts. This study provides valuable information about the strengths and weaknesses of existing spelling checkers and contributes to the improvement of spelling correction tools for Turkish. © 2024, Sakarya University. All rights reserved.
Keywords: Natural Language Processing (NLP); Spell checker; Spelling correction; Spelling errors; Turkish texts